1999
DOI: 10.1038/sj.bjc.6690305
|View full text |Cite
|
Sign up to set email alerts
|

Serum folate, homocysteine and colorectal cancer risk in women: a nested case–control study

Abstract: Summary Accumulating evidence suggests that folate, which is plentiful in vegetables and fruits, may be protective against colorectal cancer. The authors have studied the relationship of baseline levels of serum folate and homocysteine to the subsequent risk of colorectal cancer in a nested case-control study including 105 cases and 523 matched controls from the New York University Women's Health Study cohort. In univariate analyses, the cases had lower serum folate and higher serum homocysteine levels than co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
119
3
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(129 citation statements)
references
References 49 publications
4
119
3
2
Order By: Relevance
“…3,4 Data from the present analyses show that higher homocysteine is a significant risk factor for adenoma recurrence among nonusers of multivitamins. This suggests that despite folate fortification, variation remains in homocysteine that predicts adenoma risk.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…3,4 Data from the present analyses show that higher homocysteine is a significant risk factor for adenoma recurrence among nonusers of multivitamins. This suggests that despite folate fortification, variation remains in homocysteine that predicts adenoma risk.…”
Section: Discussionmentioning
confidence: 76%
“…A recent meta analysis showed a significant 20-25% lower risk of developing colorectal cancer among individuals in the highest compared to those in the lowest category of dietary folate 1 ; inverse associations between blood folate and colorectal neoplasia (i.e., cancer and adenoma) have also been shown. [2][3][4] Mechanisms responsible for the inverse association of folate on risk of colorectal cancer are not entirely understood and may involve disturbances in DNA synthesis, methylation and repair, 5-7 albeit alternate mechanisms have been proposed. 8 Homocysteine, a biochemical marker of folate status, is an amino acid that is metabolized via remethylation into methionine, facilitated by folic acid and vitamin B 12 or trans-sulfuration to cysteine, facilitated by vitamin B 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, low serum (Bird et al, 1995;Kato et al, 1999) and erythrocyte folate concentrations (Lashner, 1993;Bird et al, 1995;Paspatis et al, 1995) have been reported to be associated with the development of adenoma or cancer.…”
mentioning
confidence: 99%
“…Low folate from diet or in circulation has been associated with increased risk of colorectal cancer in several prospective studies (Giovannucci et al, 1995;Kato et al, 1999) In a cohort of 505 Chinese from Singapore, Trinh et al (2002) found that TS 3R/3R genotype was associated with reduced plasma folate and, among individuals with low dietary folate intake, with elevated plasma homocysteine levels. These results suggest that TS and methylenetetrahydrofolate reductase compete for limiting supplies of folate required for the remethylation of homocysteine.…”
Section: Discussionmentioning
confidence: 99%